Valorisation Agricole D’un Compost Produit À Partir Du Compostage En Cuve Des Déchets Municipaux - Chennaoui, M.; Salama, Y.; Makan, A.; Mountadar, M. (European Scientific Journal, ESJ, 2016)
This work is in the context of the management and recycling of solid urban waste. The evolution of the physicochemical and microbiological parameters during composting pilot scale household waste was studied. The maturity of the processes and the agronomic value of the finished product were examined. The results showed that the organic fraction of solid waste could be composted successfully in 60 days and revealing a vigorous microbial activity. The final compost has been satisfactory for its agricultural application. Phytotoxicity tests conducted on wheat and tomato crops, show that the incorporation of 25% culture support the compost allows a germination rate of up to 85% against 70% for the control for the variety of corn. In the case of tomatoes, we recorded a germination rate of about 67% against 58% for the control.